Lines of settlement: Lost landscapes within maps for future morphologies - Paul Sanders; Mirjana Lozanovska; Lana Van Galen (2021)
The value of archival documents quite often extends beyond their original purpose, as evidence contained within these artefacts, whether written or drawn, can provide veracity for new lines of heritage inquiry. Many settlements in the ‘new world’ were set out by land surveyors whose drawings charted the accurate placement and alignment of new streets and block perimeters laid upon drawings of the extant topographical landscape features. The paper discusses three settlement maps of Melbourne, Australia, through the lens of Michel de Certeau’s idea that maps are an instrument of power are not just about recording; maps are actually about appropriating and producing regimes of place. In the Australian context, the settlement drawings, prepared under the direction of the colonial administration, inadvertently depicts Country that had been under the custodial care of the First Nations peoples for millennia, and through the intentions of the settlement maps about to be irrevocably disturbed, altered or destroyed. We raise the prospect that urban and landscape design can reflect on the ‘lost landscapes’ of cultural significance, and discuss new ways of interpreting representation through an approach of design reconciliation.